Prevalence of Myocardial Fibrosis by Left Ventricular Assist Device Apical Core Biopsy and Correlation with Other Markers of Myocardial Recovery. Issue 2 (February 2019) - Schultz, Jessica; John, Ranjit; Martin, Cindy; Kamdar, Forum; Thenappan, Thenappan; Cogswell, Rebecca
Abstract : Myocardial fibrosis identified by apical core pathology at the time of left ventricular assist device (LVAD) implantation may add information regarding myocardial recovery potential. In this analysis, we report the prevalence of myocardial fibrosis by cardiomyopathy type and its association with other known markers of left ventricular recovery. Left ventricular assist device core pathology was reviewed on 332 patients who underwent LVAD implantation at a single institution between 2005 and 2016. Baseline clinical and echocardiographic characteristics were compared among patients with and without myocardial fibrosis by cardiomyopathy type. Among the 332 LVAD core specimens, myocardial fibrosis was present in 79%. Myocardial fibrosis was more common in ischemic than in nonischemic patients (90% vs . 66%; p < 0.001). Patients with fibrosis were older than those without (58 ± 12 vs . 55 ± 19; p < 0.05). Among the nonischemic cardiomyopathy cases, those with fibrosis were more likely to have an implantable cardioverter defibrillator (ICD) 81% and to be diabetic 81%. Fibrosis was not associated with left ventricular end-diastolic diameter (LVEDD), creatinine, or N-terminal prohormone of brain natriuretic peptide (NT-pro BNP). Myocardial fibrosis by apical core biopsy correlated with several known markers of left ventricular recovery including cardiomyopathy type, age, and presence of an ICD. In nonischemic cardiomyopathy patients, the degree of myocardial fibrosis may add information regarding recovery potential.